DOCK8 inhibits the immune function of neutrophils in sepsis by regulating aerobic glycolysis - Hongjun Zhu; Junlong Xu; Ke Li; Miaomiao Chen; Yueming Wu; Xian Zhang; Hua Chen; Deyuan Chen (Immunity, Inflammation and Disease, 2023)
Abstract Introduction This study endeavored to investigate the role of DOCK8 in modulating the immune function triggered by sepsis. Methods Expression of DOCK8 in the whole blood of sepsis patients and its enrichment pathways were assayed by bioinformatics. Pearson analysis was used to predict the relationship between glycolytic signaling pathway and its relevance to neutrophil function in sepsis. A sepsis mouse model was then built by performing cecal ligation and puncture treatment on male mice. Neutrophils were isolated, and their purity was tested by flow cytometry. Neutrophils were then stimulated by lipopolysaccharide to build a sepsis cell model. Next, quantitative reverse transcription polymerase chain reaction and CCK‐8 were applied to test the expression of DOCK8 and cell viability, western blot to assay the expression of HK‐2, PKM2, and LDHA proteins, ELISA to measure the concentrations of TNF‐α, IL‐1β, and IL‐6, Transwell to detect the chemotaxis of neutrophils and flow cytometry to detect the phagocytic activity of neutrophils. Finally, in different treatment groups, we used Seahorse XF 96 to analyze the extracellular acidification rate (ECAR) of sepsis cells and used enzyme‐linked immunosorbent assay to detect the contents of pyruvic acid, lactic acid, and ATP in sepsis cells. Results DOCK8 was downregulated in sepsis blood and activated neutrophils. Aerobic glycolysis was positively correlated with sepsis. Activated neutrophils promoted the expression of inflammatory factors TNF‐α, IL‐1β, and IL‐6. Low expression of DOCK8 facilitated the proliferation, chemotaxis, and phagocytic activity of sepsis cells and promoted the expression of inflammatory factors. Bioinformatics analysis revealed that DOCK8 was enriched in the glycolytic signaling pathway. Low expression of DOCK8 induced ECAR, promoted the protein expression of HK‐2, PKM2 and LDHA, and favored the increase of pyruvate, lactate, and ATP contents. While 2‐DG treatment could restore these effects. Conclusion DOCK8 may inhibit sepsis‐induced neutrophil immune function by regulating aerobic glycolysis and causing excessive inflammation, which helps to explore potential therapeutic targets.